2021
DOI: 10.14740/jcs429
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Effective Dose of 5-Aminolevulinic Acid to Protect Humans From Renal Ischemia-Reperfusion Injury: A Study in Micro Miniature Pigs

Abstract: Background: In rodent models, 5-aminolevulinic acid (5-ALA) was shown to prevent renal ischemia-reperfusion injury, but the data did not allow estimation of the human equivalent dose (HED). Therefore, this study evaluated the renal effects of 5-ALA and estimated the HED in micro miniature pigs, which have a metabolism closer to that of humans. Methods: We analyzed the efficacy and pharmacokinetics of 5-ALA by administering it to nine micro miniature pigs 2 days before renal ischemia-reperfusion injury. A patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Recently, 5-ALA has received much attention as a therapeutic agent [ 8 , 11 ] and feed additive [ 10 ]. Metabolomic analysis revealed that 5-ALA levels were significantly higher in the portal and abdominal veins of LAO1 KO mice.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, 5-ALA has received much attention as a therapeutic agent [ 8 , 11 ] and feed additive [ 10 ]. Metabolomic analysis revealed that 5-ALA levels were significantly higher in the portal and abdominal veins of LAO1 KO mice.…”
Section: Methodsmentioning
confidence: 99%
“…Protocol of a conventional model where 60 min ischemia and subsequent reperfusion injury are induced in the left kidney along with contralateral nephrectomy. This conventional protocol in which 60 min ischemia is induced by clamping left renal vessels followed by a right nephrectomy was used in the previous reports (12,20).…”
Section: Figure S1mentioning
confidence: 99%